A dynamics based analysis of allosteric modulation in heat shock proteins - Penkler, David Lawrence (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2019)
The 70 kDa and 90 kDa heat shock proteins (Hsp70 and Hsp90) are molecular chaperones that play central roles in maintaining cellular homeostasis in all organisms of life with the exception of archaea. In addition to their general chaperone function in protein quality control, Hsp70 and Hsp90 cooperate in the regulation and activity of some 200 known natively folded protein clients which include protein kinases, transcription factors and receptors, many of which are implicated as key regulators of essential signal transduction pathways. Both chaperones are considered to be large multi-domain proteins that rely on ATPase activity and co-chaperone interactions to regulate their conformational cycles for peptide binding and release. The unique positioning of Hsp90 at the crossroads of several fundamental cellular pathways coupled with its known association with diverse oncogenic peptide clients has brought the molecular chaperone under increasing interest as a potential anti-cancer target that is crucially implicated with all eight hallmarks of the disease. Current orthosteric drug discovery efforts aimed at the inhibition of the ATPase domain of Hsp90 have been limited due to high levels of associated toxicity. In an effort to circumnavigate this, the combined focus of research efforts is shifting toward alternative approaches such as interference with co-chaperone binding and the allosteric inhibition/activation of the molecular chaperone. The overriding aim of this thesis was to demonstrate how the computational technique of Perturbation response scanning (PRS) coupled with all-atom molecular dynamics simulations (MD) and dynamic residue interaction network (DRN) analysis can be used as a viable strategy to efficiently scan and accurately identify allosteric control element capable of modulating the functional dynamics of a protein. In pursuit of this goal, this thesis also contributes to the current understanding of the nucleotide dependent allosteric mechanisms at play in cellular functionality of both Hsp70 and Hsp90. All-atom MD simulations of E. coli DnaK provided evidence of nucleotide driven modulation of conformational dynamics in both the catalytically active and inactive states. PRS analysis employed on these trajectories demonstrated sensitivity toward bound nucleotide and peptide substrate, and provided evidence of a putative allosterically active intermediate state between the ATPase active and inactive conformational states. Simultaneous binding of ATP and peptide substrate was found to allosterically prime the chaperone for interstate conversion regardless of the transition direction. Detailed analysis of these allosterically primed states revealed select residue sites capable of selecting a coordinate shift towards the opposite conformational state. In an effort to validate these results, the predicted allosteric hot spot sites were cross-validated with known experimental works and found to overlap with functional sites implicated in allosteric signal propagation and ATPase activation in Hsp70. This study presented for the first time, the application of PRS as a suitable diagnostic tool for the elucidation and quantification of the allosteric potential of select residues to effect functionally relevant global conformational rearrangements. The PRS methodology described in this study was packaged within the Python programming environment in the MD-TASK software suite for command-line ease of use and made freely available. Homology modelling techniques were used to address the lack of experimental structural data for the human cytosolic isoform of Hsp90 and for the first time provided accurate full-length structural models of human Hsp90Î± in fully-closed and partially-open conformations. Long-range all-atom MD simulations of these structures revealed nucleotide driven modulation of conformational dynamics in Hsp90. Subsequent DRN and PRS analysis of these MD trajectories allowed for the quantification and elucidation of nucleotide driven allosteric modulation in the molecular chaperone. A detailed PRS analysis revealed allosteric inter-domain coupling between the extreme terminals of the chaperone in response to external force perturbations at either domain. Furthermore PRS also identified several individual residue sites that are capable of selecting conformational rearrangements towards functionally relevant states which may be considered to be putative allosteric target sites for future drug discovery efforts Molecular docking techniques were employed to investigate the modulation of conformational dynamics of human Hsp90Î± in response to ligand binding interactions at two identified allosteric sites at the C-terminal. High throughput screening of a small library of natural compounds indigenous to South Africa revealed three hit compounds at these sites: Cephalostatin 17, 20(29)-Lupene-3Î² isoferulate and 3'-Bromorubrolide F. All-atom MD simulations on these protein-ligand complexes coupled with DRN analysis and several advanced trajectory based analysis techniques provided evidence of selective allosteric modulation of Hsp90Î± conformational dynamics in response to the identity and location of the bound ligands. Ligands bound at the four-helix bundle presented as putative allosteric inhibitors of Hsp90Î±, driving conformational dynamics in favour of dimer opening and possibly dimer separation. Meanwhile, ligand interactions at an adjacent sub-pocket located near the interface between the middle and C-terminal domains demonstrated allosteric activation of the chaperone, modulating conformational dynamics in favour of the fully-closed catalytically active conformational state. Taken together, the data presented in this thesis contributes to the understanding of allosteric modulation of conformational dynamics in Hsp70 and Hsp90, and provides a suitable platform for future biochemical and drug discovery studies. Furthermore, the molecular docking and computational identification of allosteric compounds with suitable binding affinity for allosteric sites at the CTD of human Hsp90Î± provide for the first time "proof-of-principle" for the use of PRS in conjunction with MD simulations and DRN analysis as a suitable method for the rapid identification of allosteric sites in proteins that can be probed by small molecule interaction. The data presented in this section could pave the way for future allosteric drug discovery studies for the treatment of Hsp90 associated pathologies.
Keywords: Heat shock proteins; Molecular chaperones; Allosteric regulation; Homeostasis; Protein kinases; Transcription factors; Adenosine triphosphatase; Cancer -- Chemotherapy; Molecular dynamics; High throughput screening (Drug development)